Fundamental topics in plastic surgery - Marré, Diego (Thieme, 2018)
Given the wide-ranging nature of the literature one must study in plastic surgery training, a solid grounding in many fundamental principles and procedures is an absolute prerequisite to becoming a competent plastic surgeon. And yet, until now there has been no single source that collects these fundamental topics in one volume; rather, the information has had to be gleaned from the introductory chapters of multiple comprehensive textbooks. The present volume takes a new approach, and provides the trainee an opportunity to learn these fundamentals more efficiently and comprehensively through a.